â€œBisa Bawa Pacar Engga?â€ Sociological Analysis of Rules-Free and Strict-Rules Boarding Houses in Gorontalo - Wiroto, Dondick Wicaksono; Ibrahim, Ridwan; Rahmatiah, Rahmatiah; Setiawan, Aris (Universitas Negeri Semarang, 2021)
This research was based on the phenomenon of free sex behavior by students in their boarding houses, hence the existence of the term 'rules-free' and 'strict-rules' boarding houses. This phenomenon was interesting to study using the concept of behavior so that it can be understood sociologically how the two concepts of the boarding house are related. Grounded theory was used in this research in the hope that the construction of social control in the boarding house arises from the expressions and beliefs, experiences, feelings, and goals of the owner and the occupants. The results showed that students' deviant behavior in the form of free sex was caused by four factors, namely the absence of enforcement of the rules in the boarding house by the owner, students' weak self-control, the arrangement of boarding houses was hidden from society, and negative labeling formed by a stigma. This research concluded that self-control in a boarding house is not formed by awareness to uphold social norms, but is more prompted by one's desire to avoid being embarrassed.